Literature Study: Effect of Jigsaw Assisted with Mind Map on Students Learning Competencies - Monhartini, Monhartini; Helendra, Helendra; Syamsurizal, Syamsurizal; Alberida, Heffi (Bioedukasi: Jurnal Pendidikan Biologi, 2021)
This article review aims to look at the effect of applying the jigsaw type cooperative learning model assisted with mind map recitation on students' learning competencies. The method used is a systematic review by reviewing articles that are relevant to the author's research. The data used is obtained from relevant journals that are relevant to the problem the authors discuss. Data is taken from databases such as SINTA, Google Scholar and other relevant journal websites. The variables used in this study are the type of jigsaw cooperative learning model (independent variable) and the students' learning competency (dependent variable). Starting from elementary school level, junior high school, high school, to college can also feel the positive influence of the application of this type of cooperative learning model jigsaw. Because of the positive influence of the application of this type of jigsaw cooperative learning model, it is expected that the teacher will apply the material that is both theoretical and practical. This type of jigsaw cooperative learning method can improve student learning outcomes and activeness so that problems that occur in the learning process can be overcome.